Peak-to-Average Power Ratio Reduction Based on Penalty-CCCP for Filter Bank Multicarrier Systems - Cui, Fangyu; Cai, Yunlong; Zhao, Minjian; Lei, Ming; Hanzo, Lajos (IEEE transactions on vehicular technology, 2019)
Filter bank multicarrier (FBMC) has received substantial research attention as benefit of its low out-of-band emission and high spectral efficiency. However, a main challenge of FBMC is its relatively high peak-to-average power ratio (PAPR). Hence we formulate an optimization problem for the PAPR reduction of FBMC signals, where the PAPR is minimized subject to the constraints of symbol distortion and dummy subcarrier power used for PAPR-reduction. In order to tackle the highly coupled nonconvex problem, we convert the original problem into a more tractable yet equivalent form and then propose a novel algorithm based on the penalty concave-convex procedure (penalty-CCCP). Our simulation results show that the proposed algorithm substantially reduces the PAPR compared to conventional techniques.